Saddle Pulmonary Embolism in Patients with Cancer in the Era of Incidental Events: Clinical Findings and Outcomes in a Single Centre Cohort - Aramberri, Mario; Benegas, Mariana; Sanchez, Marcelo; Muñoz-Guglielmetti, Diego; Zamora, Carles; García-Villa, Adrián; Diaz-Pedroche, Carmen; Font, Carme (TH Open, 2022)
Background There is scarce information regarding the prevalence and clinical impact of saddle pulmonary embolism (PE) in patients with cancer.Objectives This study aimed to assess the prevalence, clinical findings, and short-term outcomes of patients with cancer-related saddle PE including acute symptomatic and unsuspected events.Patients/Methods Consecutive patients with cancer-related PE (March 1, 2006–October 31, 2014) were retrospectively reviewed by a chest radiologist to assess PE burden and signs of right ventricular (RV) overload. The clinical outcomes within 30 days were evaluated according to saddle versus nonsaddle PE.Results Thirty-six (12%) out of 289 patients with newly diagnosed cancer-related PE presented with saddle PE. Saddle PE was found in 21 cases (58%) with acute symptomatic PE and the remaining 15 cases (42%) were found as unsuspected findings. Patients with saddle PE had more frequently experienced a previous thrombotic event (31 vs. 13%; p = 0.008), and it occurred more frequently as an acute symptomatic event (58 vs. 39%; p = 0.025) compared with those with nonsaddle PE. Signs of RV overload including RV/left ventricle ratio ≥1 (22 vs. 4%; p < 0.001) and interventricular septum displacement (53 vs. 20%; p < 0.001) were also more common in patients with saddle PE compared with nonsaddle PE. Overall, PE-related mortality, venous thromboembolism recurrence, and major bleeding within 30 days were found to be similar according to saddle versus nonsaddle PE.Conclusion Saddle PE is not uncommon in patients with cancer-related PE including in those with unsuspected PE. Similar 30-day outcomes were found according to saddle versus nonsaddle PE in our cohort.
Keywords: cancer; incidental findings; pulmonary embolism; thrombosis; venous thromboembolism